Implementación en Simul8 de un modelo genérico de simulación discreta de los servicios ambulatorios y de hospitalización en los hospitales del Reino Unido (2013)
In 2007 Günal and Pidd developed a generic discrete simulation model to represent hospitals in the UK in order to investigate possible improvements for hospital’s performance. They divided the model in three principal sub-models: Accidents and emergency, outpatient and inpatient. This article presents an implementation in Simul8 of the inpatient sub-model, a simulation software that offers an friendly graphic and interactive component that makes the model probably more accessible to people unrelated to the simulation topic. This article also analyses the generic component of the model looking forward to a possible application in Colombian hospitals.